A common variant of CNTNAP2 is associated with sub-threshold autistic traits and intellectual disability - Shiota, Yuka; Hirosawa, Tetsu; Yoshimura, Yuko; Tanaka, Sanae; Hasegawa, Chiaki; Iwasaki, Sumie; An, Kyung-min; Soma, Daiki; Sano, Masuhiko; Yokoyama, Shigeru; Kikuchi, Mitsuru (PloS one, 2021)
Sub-threshold autistic traits are common in the general population. Children with sub-threshold autistic traits have difficulties with social adaptation. Contactin-associated protein-like 2 ( CNTNAP2 ) is associated with the development of Autism spectrum disorder (ASD) and the single-nucleotide polymorphism rs2710102 (G/A) of CNTNAP2 is suggested to contribute to sub-threshold social impairments and intellectual disabilities. We recruited 67 children with Autistic disorder (AD) (49 boys, 18 girls, aged 38–98 months) and 57 typically developing (TD) children (34 boys, 23 girls, aged 53–90 months). We assessed the participants’ intelligence and social reciprocity using the Kaufman Assessment Battery for Children (K-ABC) and the Social Responsiveness Scale (SRS), respectively. Genomic DNA was extracted from the buccal mucosa and genotyped for rs2710102. A chi-square test revealed a significant association between genotype and group [χ 2 (2) = 6.56, p = 0.038]. When a co-dominant model was assumed, the results from linear regression models demonstrated that TD children with A-carriers (AA + AG) presented higher SRS T-scores [t(55) = 2.11, p = 0 . 039 ] and lower simultaneous processing scale scores of K-ABC [t(55) = -2.19, p = 0 . 032 ] than those with GG homozygotes. These associations were not significant in children with ASD. TD children with the rs2710102 A-allele may have more sub-threshold autistic traits than those with GG homozygotes, reflected in higher SRS scores and lower simultaneous processing scale scores. These results support the use of genetic evidence to detect sub-threshold autistic traits.